OPEN INNOVATION THEORY: DEFINITION, INSTRUMENTS, FRAMEWORKS - L. S. Orlova (Стратегические решения и риск-менеджмент)
Today flexibility is becoming one of the most important capability in business, because the product life cycle is reduced, the external environment of organizations is constantly changing, technologies are improving every day. In such circumstances, companies cannot afford to develop technologies exclusively in R&D departments in their companies; this is unproductive, inefficient and expensive. Companies “opened” their innovation processes to improve their innovation potential. The relevance of this work is due to the great interest of both the scientific community and practitioners in the instruments and strategies needed for successful adoption of the theory of open innovation.The objective of this study is to provide a comprehensive review of the progress on open innovation literature reflecting the most essential topics to be covered in future research. This survey study makes a significant contribution to the research of the open innovation theory. The article offers a detailed overview of the various views and studies related to this topic. The evolution in the field of research of open innovation theory is presented here. The article is structured as follows: the link between open innovation and other theories in management, the adoption of open innovation paradigm in different industries, the influence of adopting the open innovation theory on the business, criticism of the open innovation theory, researches studying open innovation theory conducted in Russia, classification of frameworks in the open innovation theory. This article describes the state of open innovation at the intersection of research, practice, and policy.In addition, this work focuses on the most cited publications of the most cited scientists, as well as on the work of the last two to three years.We combinebibliographic analysis of all papers on the topic published in Scopus database witha systematic content analysis of the field to develop a deeper understanding of earlier work.